360° angular coverage pattern and polarization diversities wideband circularly polarized multiple input multiple output antennas. Issue 2 (18th November 2021) - Chaudhary, Prashant; Kumar, Ashwani; Kumar, Pramod; Patel, Kamlesh; Arya, Ravi Kumar; Verma, Anand Kumar
Abstract: This article presents a new design of six‐element prism and eight‐element cubic circularly polarized multiple input multiple output (MIMO) antennas exhibiting pattern and polarization diversity characteristics. The proposed antennas have 360° angular coverage. Each element of the MIMO antenna is radiating power in a different direction; antenna‐1 radiates in −30°, antenna‐2 radiates in 30°, antenna‐3 radiates in 60°, and antenna‐4 radiates in 120°. Antenna‐5 radiates in 150°, antenna‐6 radiates in −150°, antenna‐7 radiates in −120°, and antenna‐8 radiates in −60°.The radiation pattern can be directed in a specific direction by exciting the particular antenna element. It has wideband circular polarization in X‐band (8.0–11.8 GHz). The proposed MIMO antenna element consists of pairs of mirrored monopole antennas facing each other are configured in the form of the prism and cube. The chance of mutual coupling is very high in both the configuration. A hollow copper cylinder is placed inside the prism and cube to reduce the mutual coupling. The isolation between the antennas is found better than −24 dB. The impedance matching bandwidth is 3.8 GHz (8–11.8 GHz), and the 3 dB axial ratio bandwidth is 2.69 GHz (8.01–10.7 GHz). The envelope correlation coefficient is less than 0.09, and total active reflection coefficient is less than −10 dB in a wide bandwidth. High isolation and uncorrelated radiation patterns between the adjacent elements make the proposed six‐element and eight‐element antenna a good candidate for massive MIMO antenna systems. The size of the antenna is 38.8 × 38.8 × 23 mm 3, and this compact MIMO antenna is useful for X‐band communication.